World of inventors : Alexander Graham Bell - Honovich, Nancy; Dawson, Scott (California : Silver Dolphins, 2008)
Can you hear me now? These days we take for granted the accessibility of the cell phone and how easy it is to talk to someone on the other side of the world. Alexander Graham Bell spent his life trying to devise new and better ways for people to communicate, first as a teacher for the deaf, and later as an inventor of many important devices, most notably the telephone. Young readers will be enthralled by World of Inventors: Alexander Graham Bell, which chronicles Bell's life and some of his amazing inventions. Inspired, kids can then build their own intercom system based on one of Bell's designs.
Keywords: American history -- Non-fiction